Experimental study of impulse sound transmission between rooms. Issue 3 (September 2022) - Kanev, Nikolay; Fadeev, Alexander
This paper presents experimental results of a study of the sound transmission between two rooms in one of which an intensive short impulse is radiated. The room with the source is treated by a sound absorber to reduce reflections and provide a pure impulse impact on a partition separating the rooms. The influences of the source and receiver positions, acoustic conditions in the receiver room and energy of the impulse are investigated and analyzed. It has been shown that all these factors affect the impulse sound transmission, which is proposed to be described by two coefficients. The first one is a ratio of peak sound pressure values in both rooms, the second one is the similar ratio only for peak-to-peak values. Some results correlate with theoretical assumptions, but the others differ significantly. So, the theoretical approaches to the impulse sound transmission or dynamic transmission loss need to be developed as well as the impulse sound insulation of building elements should be clearly defined and studied.